(untitled) (Journal SCIENCEVOLUTION, 2025)
The objective was to design and implement a remotely controlled mobile robot prototype for the preliminary detection of methane gas (CH4) leaks, intended for use in confined or industrial risk environments to reduce human exposure. The project was developed under a descriptive–demonstrative technological approach, with a controlled experimental design conducted in the laboratory and framed within applied research. A real-time data detection and transmission system was implemented using the MQ-4 sensor and the ESP8266-01 module, connected to an Arduino UNO R3 board with an ATmega328P microcontroller. The motion control system was implemented and verified through the H-bridge L293D and commands issued from a mobile application. The stable operation of the MQTT communication system was confirmed, and its operational autonomy was evaluated using lithium batteries. The system showed an effective response to motion commands programmed in C++, as well as successful remote detection of simulated CH4 variations. The resulting prototype proved to be functional, low-cost, and replicable. Future improvements are proposed regarding sensor calibration, energy autonomy optimization, and the integration of autonomous navigation algorithms.